Ecology without Culture : Aesthetics for a Toxic World - Marran, Christine L. (Book collections on Project MUSE., 2017)
"Cultures have long defined themselves through biological elements to prove their strength and longevity, from cherry blossoms in Japan to amber waves of grain in the United States. In Ecology without Culture, Christine L. Marran introduces the concept of biotropes--material and semiotic figures that exist for human perception--to navigate how and why the material world has proven to be such an effective medium for representing culture. A bold and timely reconsideration of ecocriticism, Ecology without Culture insists on decentering questions of culture to highlight the materiality of poetry, film, and prose fiction. Marran argues that ecocriticism can critique ecological realities more effectively from outside the frame of human exceptionalism. Through discussions of primarily non-Anglophone literature, poetry, and cinema about toxic events in contemporary history-- from the depiction of slow violence in documentary by Tsuchimoto Noriaki to the powerful poetry of Ishimure Michiko--Marran argues that ecocriticism must find a way to engage culture without making the perpetuation of ethnos and anthropos the endgame of ecopolitics. Using the biological foundations and geological time scales of textual worlds to more deeply critique cultural humanism, Marran ultimately contends that the chief stumbling block to ecological thinking is not the image of nature, but the image of culture"--